Exploring health-seeking behavior for non-communicable chronic conditions in northern Bangladesh - Rasul, Fatema; Sarker, Malabika; Yasmin, Farzana; De Allegri, Manuela (PLoS global public health, 2022)
Non-communicable Diseases (NCDs) account for 67% of total deaths in Bangladesh. However, the Bangladeshi health system is inadequately prepared to tackle NCDs. Evidence on NCD-specific health-seeking behavior can help appropriately address the needs of people affected by NCDs in Bangladesh. Our study aims to explore health-seeking behavior for people affected by NCDs in northern Bangladesh. We conducted a qualitative study in Mithapukur, Rangpur, during 2015-2016. We purposely selected respondents and carried out 25 in-depth interviews with individuals affected by non-communicable diseases and 21 healthcare providers. Additionally, we held six focus group discussions in the wider community. We verbatim transcribed all interviews and analyzed the content using thematic analysis, according to the following thematic areas: individual, household, and contextual factors that influence health-seeking behavior for NCDs within the context of the broader socio-economic environment. Study findings indicate that people seek care only when symptoms disrupt their daily lifestyle. Henceforth, people’s health beliefs, religious beliefs, and relations with local providers direct their actions, keeping provider accessibility, cost anticipation, and satisfying provider-encounters in mind. Health-seeking is predominantly delayed and fragmented. Semi-qualified providers represent a popular first choice. Gender roles dominate health-seeking behavior as women need their guardian’s permission to avail care. Our findings indicate the need to sensitize people about the importance of early health-seeking for NCDs, and continuing life-long NCD treatment. Our findings also highlight the need for people-centered care, making preventive and curative NCD services accessible at grassroots level, along with relevant provider training. Furthermore, special provisions, such as financial support and outreach programs are needed to enable access to NCD care for women and the poor.
Gesehen am 06.07.2022